Patient safety in computed tomography services: an integrative review - Késsya Dantas Diniz; Isabelle Katherinne Fernandes Costa; Richardson Augusto Rosendo da Silva (Universidade Federal de Goias, 2016)
The objective was to identify essential elements to offer a safe assistance to patients submitted to computed tomography scan. An integrative literature review on Medline, SCOPUS, Web of Science and CINAHL databases, guided by the question: what are the essential elements to offer a safe assistance to the patient submitted to computed tomography scan? We selected twenty-three articles, from those, 50% addressed optimization, monitoring, quality and protection about radiation dose exposition; 25% focused on the contrast used for tomography; and 25% concentrated on nursing care and management of individual cases. The evidence for safe assistance to the patient submitted to computed tomography points to need to minimize the conduction of unnecessary exams, and consequently exposition to radiation, to guarantee the radiological protection, to provide adequate care for adverse reactions, qualified human resources and trustful quality indicators for assistance.